Gamma-tocotrienol reverses nicotine-induced oxidatives stress-related in vitro and in vivo embryonic development and pregnancy outcome in mice / Yuhaniza Shafinie Kamsani - Kamsani, Yuhaniza Shafinie (Institute of Graduate Studies, UiTM, 2014)
A study to evaluate the effects of nicotine and simultaneous supplementation of γ-tocotrienol (γ-TCT), one of the four isomers in tocotrienols (TCT), and nicotine, on in vitro and in vivo embryonic development in mice (Mus musculus) had been carried out. Several approaches were undertaken including an investigation on in vitro effects of various doses and durations of nicotine treatment on pre-implantation embryonic development. Results showed that nicotine treatment decreased the number of retrieved embryos, resulted embryo degeneration, delayed embryo cleavage, induced disproportionate size of blastomeres and degraded blastomeres (p<0.05). Moreover, the deleterious impact of nicotine on pre-implantation embryonic development was dose- and treatment duration-dependent with a corresponding increase in plasma malondialdehyde (MDA) concentrations (p<0.05). Based on this finding, the study was further elucidated in terms of examining the dose-related beneficial effects of γ–TCT in nicotineinduced cessation of pre-implantation embryonic development in vitro.